Global Disinformation: Political and Economic Origins - Díez Medrano, Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The paper entitled "Global Disinformation: Political and Economic Origins" locates and analyses the historical milestones that have led to the existence of information control and its interested manipulation, with the purpose of controlling and dominating the whole of civilization from political and economic power. This analysis reveals the tools and procedures geared to explain the state of growing misinformation against which citizens rebel at a global level, perceiving a threat to freedom of information, as well as against the set of fundamental freedoms of the individual.